Comparative Effectiveness of Primary Prevention Implantable Cardioverter‐Defibrillators in Older Heart Failure Patients With Diabetes Mellitus. Issue 12 (16th June 2020) - Sharma, Abhinav; Wu, Jingjing; Xu, Haolin; Hernandez, Adrian; Felker, G. Michael; Al‐Khatib, Sana; Green, Jennifer; Matsouaka, Roland; Fonarow, Gregg C.; Singh, Jagmeet P.; Heidenreich, Paul A.; Ezekowitz, Justin A.; et al.
Abstract : Background: There are conflicting data regarding the benefit of primary prevention implantable cardioverter‐defibrillators (ICDs) in patients with diabetes mellitus and heart failure (HF) with reduced ejection fraction. We aimed to assess the comparative effectiveness of ICD placement in patients with diabetes mellitus and HF with reduced ejection fraction. Methods and Results: Data were obtained from the Get With the Guidelines–Health Failure registry, linked with claims from the Centers for Medicare & Medicaid Services. We used a Cox proportional hazards model censored at 5 years with propensity score matching. Of the 17 186 patients with HF with reduced ejection fraction from the Centers for Medicare & Medicaid Services claims database (6540 with diabetes mellitus; 38%), 1677 (646 with diabetes mellitus; 39%) received an ICD during their index HF hospitalization or were prescribed an ICD at discharge. Patients with diabetes mellitus and an ICD (n=646), as compared with those without an ICD (n=1031), were more likely to be younger (74 versus 78 years of age) and have coronary artery disease (68% versus 60%). After propensity matching, ICD use among patients with diabetes mellitus, as compared with those without an ICD, was associated with a reduced risk of all‐cause mortality at 5 years after HF discharge (54% versus 59%; multivariable hazard ratio, 0.73; 95% CI, 0.64–0.82; P <0.0001). Ischemic heart disease did not modify the association between ICD use and all‐cause mortality ( P =0.95 for interaction). Similar results were seen in patients without diabetes mellitus. Conclusions: Primary prevention ICD use among older patients with HF with reduced ejection fraction and diabetes mellitus was associated with a reduced risk of all‐cause mortality. Our analysis supports current guideline recommendations for implantation of primary prevention ICDs among older patients with diabetes mellitus and HF with reduced ejection fraction.